Solvent fermentation from palm oil mill effluent using clostridium acetobutylicum in oscillatory flow bioreactor - Takriff, M.S; Masngut; N.Kadhum; A.A.H; Khalil, M.S; Mohammad, A.W (Universiti Kebangsaan Malaysia, 2009)
Acetone-butanol-ethanol (ABE) fermentation from Palm Oil Mill Effluent (POME) by C. acetobutylicum NCIMB 13357 in an oscillatory flow bioreactor was investigated. Experimental works were conducted in a U-shaped stainless steel oscillatory flow bioreactor at oscillation frequency between 0.45-0.78 Hz and a constant amplitude of 12.5 mm. Fermentations were carried out for 72 hr at 35oC using palm oil mill effluent and reinforced clostridia medium as a growth medium in batch culture. Result of this investigation showed that POME is a viable media for ABE fermentation and oscillatory flow bioreactor has an excellent potential as an alternative fermentation device.